2020
DOI: 10.1200/jco.20.01924
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitors in the Management of Ovarian Cancer: ASCO Guideline

Abstract: PURPOSE To provide recommendations on the use of poly(ADP-ribose) polymerase inhibitors (PARPis) for management of epithelial ovarian, tubal, or primary peritoneal cancer (EOC). METHODS Randomized, controlled, and open-labeled trials published from 2011 through 2020 were identified in a literature search. Guideline recommendations were based on the review of the evidence, US Food and Drug Administration approvals, and consensus when evidence was lacking. RESULTS The systematic review identified 17 eligible tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
123
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 203 publications
(138 citation statements)
references
References 41 publications
1
123
0
1
Order By: Relevance
“…Interestingly, two recent reports have suggested an association between decreased MDSCs and favorable treatment outcomes in ovarian cancer patients. Lee et al showed that germline BRCA1 and 2 mutation-associated ovarian cancer, which is believed to have higher response rates to platinum-based chemotherapy than BRCA wild-type [34], has fewer circulating MDSCs and higher CD8 + T cells in PBMC compared with BRCA wildtype ovarian cancer [24]. Second, Li et al demonstrated that metformin treatment in diabetic patients with ovarian cancer was associated with reduced circulating MDSCs, a concomitant increase in the circulating CD8 + T cells, and longer survival [29].…”
Section: The Frequency Of Mdscs As a Prognostic Indicator Or A Biomarmentioning
confidence: 99%
“…Interestingly, two recent reports have suggested an association between decreased MDSCs and favorable treatment outcomes in ovarian cancer patients. Lee et al showed that germline BRCA1 and 2 mutation-associated ovarian cancer, which is believed to have higher response rates to platinum-based chemotherapy than BRCA wild-type [34], has fewer circulating MDSCs and higher CD8 + T cells in PBMC compared with BRCA wildtype ovarian cancer [24]. Second, Li et al demonstrated that metformin treatment in diabetic patients with ovarian cancer was associated with reduced circulating MDSCs, a concomitant increase in the circulating CD8 + T cells, and longer survival [29].…”
Section: The Frequency Of Mdscs As a Prognostic Indicator Or A Biomarmentioning
confidence: 99%
“…Currently, PARPi have been implemented in the clinical standards as maintenance therapy in first line BRCA mutated high grade serous ovarian cancer (HGSOC) stages III and IV after partial or complete response to platinum salts, in II line and onward for platinum sensitive relapsed high grade serous or endometrioid OC (4).…”
Section: Background and State Of The Artmentioning
confidence: 99%
“…For example, due to early pathogenic mutations in the TP53 gene, the tumor genome is largely unstable with a progressive increase in different kinds of structural aberrations. In this scenario, biological information provided by the single primary tumor biopsy at diagnosis, when the tumor is naive to chemotherapy, does not allow us to identify those sub-clonal molecular alterations, e.g., reversion of somatic BRCA mutations, which may have been developed in the metachronous lesions, thus characterizing the genome of relapsed disease and its resistance to conventional drugs [30][31][32].…”
Section: Liquid Biopsy In Ovarian Cancermentioning
confidence: 99%